Report of a case of ectopic pregnancy in non-communicating rudimentary horn of unicornuate uterus - Seyede Houra Mousavi Vahed; Mahsa Dehghani; Seyedeh Azam Pourhoseini; Rahele Ebrahimi (Mashhad University of Medical Sciences, 2020)
Introduction: Uterine anomalies are caused by impairment in the formation, evolution, or defect in the connection of Mullerian bud in the embryonic period, and the prevalence of these disorders is 2% to 4% in the population of women of reproductive age. Unicornuate uterus is one of the types of uterine anomalies in which one of the Mullerian ducts has normal growth, and therefore a normal cavity is formed along with the uterine and vascular tract, but different degrees of growth disturbance is seen in the other Mullerian duct (from no growth to existence of rudimentary horn with or without cavity and so on). One of the complications of uterine development disorders is pregnancy in rudimentary horn. Case presentation: The patient was a 17-year-old woman with ectopic pregnancy in non-communicating rudimentary horn of unicornuate uterus that was mistakenly diagnosed as an ectopic pregnancy in a normal fallopian tube and treated with methotrexate and was referred as a persistent ectopic pregnancy and no response to methotrexate for surgical treatment. The patient underwent laparoscopy and then with diagnosis of pregnancy in the unrelated anterior horn, the pregnancy products and the left tube were removed and the left ovary was preserved. The patient was discharged after 2 days with good general condition. Conclusion: In the case of initial diagnosis of ectopic pregnancy, precise follow-up should be performed in terms of decrease in beta-HCG circulation; in the case of no increase in beta-HCG or if beta-HCG was stable despite methotrexate treatment, further investigations through Ultrasound, MRI, laparoscopy, and hysteroscopy be performed to diagnose uterine anomalies. The presence of uterine rudimentary horn in cases of stable ectopic pregnancy, despite being rare should be considered as one of the possible cases and the patient is transferred to operation room with previous preparation.